Treasure the beautiful things in life - The Victoria Mutual Building Society (Kingston : The Victoria Mutual Building Society, 1986)
Done by The Victoria Mutual Building Society in 1986 showing photographs of two flowers.
Keywords: The Victoria Mutual Building Society -- Jamaica; Calendars -- Jamaica; Flowers -- Jamaica